STRATEGY OF BUSINESS INNOVATION IN SYARI’AH BANKS CASE STUDY OF THE FINANCING TRANSACTION MODEL IN BANK BJM SYARI’AH‘S PRODUCTS SURABAYA - Ismail Nawawi (Journal of Economics, Business, and Accountancy Ventura, 2012)
This research attempts to analyze the model in Shariah banking business innovation strategy andits application. This research used the qualitative method, in which the data were collected byobservation, interviews and documentary study. These data were chosen purposively and snowballing,consisting of the Managing Director, Director of Operations and Marketing DirectorBJM Bank Surabaya. These data were analyzed using Thesis (theory and data), antithesis (dataand theory) and synthesis (analysis), in addition, also using process analysis data reduction andverification. It shows that the model of financing in Bank BJM shariah Surabaya using, (1) theprinciple of surrogate form of demand deposits (wadi'ah), (2) the principle of sharing and distributionof fund management, (3) the principle of sale and mark- up with a lump sum credit score(taqsid), (4) the principle of lease (ijara), a pure rental and leasing, (5) the principle of fee serviceslike clearing, collection, transfers and others. In doing strategy, it must be done by lookingat the object of the customers' needs, a given customer financing, investment, and ability to understandthe customer. Such strategy was done by category facilitated by profit sharing (mudaraba)and partnership (Musharaka), while the distribution of the benefits of the activities of productionby the sale (murabaha, salam and Isthisna').